Enteral nutrition: our experience with percutaneous endoscopic gastrostomy (PEG) and revision of literature - Tommasello, G.; Bellavia, M.; Damiano, et al., G. (Progress in Nutrition, 2012)
Enteral nutrition (EN), as parenteral nutrition (PN), can be used in cases of patients whose medical conditions prevent the intake of food by mouth; unlike PN, EN keeps the functionality of the digestive tract and it makes home management of patients easier. However, the experience and literature have documented a number of serious complications, fortunately rare, which depend on the methods used in EN realization.We report in this paper our experience in 44 cases of percutaneous endoscopic gastrostomy (PEG), concluding that it is a safe and complications-free procedure. We believe that a nutritional intervention is indicated when, improving nutritional status, patients can obtain a better quality of life and have an average life expectancy. La nutrizione enterale: nostra esperienza con la gastrostomia percutanea per via endoscopica e revisione della letteratura Riassunto La nutrizione enterale, così come quella parenterale, è indicata in quei pazienti le cui condizioni cliniche generali non permettono l’assunzione di cibo per via orale, ma a differenza di quest’ultima preserva la funzionalità del tratto digestivo e rende più facile la gestione domiciliare del paziente. Dalla letteratura è comunque noto che alcune particolari procedure di realizzazione della nutrizione enterale sono associate a complicanze anche severe, sebbene con una rara incidenza. In questo lavoro descriviamo la nostra esperienza nella realizzazione di 44 gastrostomie percutanee per via endoscopica, concludendo che la tecnica da noi utilizzata è sicura e priva di complicanze significative. Sulla base della nostra esperienza, e di una attenta revisione della letteratura, riteniamo che un intervento nutrizionale sia da consigliare nei pazienti con una aspettativa di vita media, qualora ciò contribuisca ad un miglioramento significativo della qualità di vita.